Use of vibratory shear enhanced processing to treat magnetic ion exchange concentrate: A techno-economic analysis - Leong, J.; Tan, J.; Heitz, Anna; Ladewig, B. (2016)
Disposal of waste generated by inland water treatment technologies is highly expensive. The introduction of vibratory shear enhanced processing (VSEP) to treat waste produced from magnetic ion exchange (MIEX) shows benefits in terms of performance and economics. A small VSEP unit fitted with a nanofiltration (NF) membrane is capable of treating up to 15. kL of MIEX waste per day, is able remove more than 97% of dissolved organic compounds as well as recover over 80% of waste in the form of permeate. The reuse of permeate to makeup brine has seen significant reductions in salt consumption and waste disposal at Wanneroo Groundwater Treatment Plant (GWTP). During the first year of VSEP operation, salt consumption reduced by 42% and waste disposal was projected to reduce by 23.9%. Further improvements in both cost categories were observed in the second year of operation and considering the same trend is followed, the payback period of the project will occur between the 6th and 7th year of operation for discounted analysis and has a positive net present value.